A three-channel fluorescent probe to image mitochondrial stress. Issue 56 (11th June 2020) - Niu, Huawei; Tang, Jun; Zhu, Xiaofei; Li, Zipeng; Zhang, Yongru; Ye, Yong; Zhao, Yufen
Abstract : A two-photon fluorescent probe NPClA was developed for imaging mitochondrial stress. Abstract : Dual-recognition probes based on one reacting site inevitably encounter competition problems. Here, NPClA, a two-photon fluorescent probe based on a dual-site response for SO2 /HOCl, was developed and applied in imaging mitochondrial stress.